Answers

2016-06-28T22:18:24+08:00
JUST wait ok?..........
1 2 1
2016-06-28T23:33:42+08:00
To find the cube of a binomial:
1st term = cube of the first term of the factors = x³
2nd term = thrice the product of the square of the first term and second term of the factors = 3[(x²)(6)]
3rd term = thrice the product of the square of the second term and the first term = 3[(x)(6)²]
4th term = cube of the second term = 6³
SOLUTION:
(x+6)³ = (x)³ + 3[(x²)(6)] + 3[(x)(6)²] + 6³ = x³ + 18x² + 108x + 216

Remember that the answer of the cube of a binomial has always 4 terms. 







0